The cost of providing primary health‐care services from a needle and syringe program: A case study. (29th November 2012) - Islam, M. Mofizul; Shanahan, Marian; Topp, Libby; Conigrave, Katherine M.; White, Ann; Day, Carolyn A.
Abstract Introduction and Aims Targeted primary health‐care services for injecting drug users have been established in several countries to reduce barriers to health care, subsequent poor health outcomes and the considerable costs of emergency treatment. The long‐term sustainability of such services depends on the resources required and the coverage provided. This study assesses the additional cost required to operate a nurse‐led primary health care in an existing needle syringe program setting, estimates the costs per occasion of service and identifies key factors influencing improved service utilisation. Design and Methods Using standard costing methods and the funder perspective, this study estimates costs using the 'ingredients' approach where the costs of inputs are based on quantities and unit prices (the ingredients). Results During the 2009–2010 fiscal year, the primary health‐care clinic provided 1252 occasions of service to 220 individuals, who each made an average of 3.9 presentations. A total cost of AU$250 626 was incurred, 69% of which was for personnel and 22% for pathology. During the study period the average cost per occasion of service was AU$199.96, which could be as low as AU$93.32 if the clinic reached its full utilisation level. Discussion and Conclusions Although the average number of presentations per client was satisfactory, the clinic was underutilised during the study period. Proactive engagement of clients at the needle syringe program shopfront and an increased range of services offered by the clinic may help to attract more clients.